The Relationship Between Mothers’ Characteristics and Mothers’ Level of Knowledge About Children’s Diet in Overweight Children With A Risk of Diabetes Mellitus in An Elementary School in Tangerang - Tehuajo, Aunike Paquita; Leviana, Rachel Aprilia; Damayanti, Yoela; Arkianti, Maria Maxmila Yoche; Fangidae, Erniyati (Journal of Nursing Science Update (JNSU), 2023)
Diabetes Mellitus (DM) is a disease characterized by high blood sugar levels that could occur in school-age children. One of the risk factors of DM is being overweight, which is influenced by an unbalanced diet. Good knowledge of mothers in providing good nutritional intake to overweight children can reduce the risk of DM in children. This study aims to identify the relationship between mothers’ characteristics (age, occupation, education level, exposure to information from mass media, and family history of DM) and mothers’ level of knowledge about the diet of overweight children with the risk of DM in children aged 6-12 years in an elementary school in Tangerang. This study used a descriptive quantitative method with univariate and bivariate analysis. A purposive sampling of 31 mothers with overweight children was involved. The research instrument was a questionnaire measuring the mothers' level of knowledge about the diet of overweight children with a risk of DM. The results showed that only education level revealed a relationship with mothers’ level of knowledge (p-value <0.05), while other characteristics indicated no relationship (p-value > 0.05). Increasing mothers ‘knowledge about healthy diets for children can be obtained from formal education, but non-formal education also plays an important role. Schools can reach out to health units to provide health education about the diet of school-age children and provide a clean and healthy canteen. Further research should identify other factors influencing the mother's knowledge level.